Perancangan dan Pengembangan Sistem Informasi Monitoring Sewa ATM Berbasis Web Menggunakan Metode SDLC - Rizky Darmawan; Bias Yulisa Geni (Journal of Information System Research (JOSH), 2023)
Several bank institutions in Indonesia often experience obstacles in the process of processing data and information monitoring ATM rentals. The purpose of this research is to facilitate the process of processing data and monitoring related to ATM rentals to be more practical, efficient, and accurate in order to reduce errors that often occur when using the previous system. The data collection method used in this study is by observing and interviewing with parties involved in the administration of the ATM rental process. Based on the problems in the bank that is still doing manual data collection for ATM rental activities, namely by processing data in Microsoft Excel. In designing the system, the method used in this study is the Software Development Life Cycle (SDLC) method and uses the Codeigniter PHP Framework. Web-based ATM rental monitoring information system using the SDLC method is able to provide solutions to problems that often occur in the ATM rental process, and with this web-based monitoring system, it can maximize the monitoring process and improve the data collection process for the better. ATM rental activities can also run effectively and efficiently and are able to solve problems that often occur in the bank. This web-based monitoring information system using the SDLC method can also be developed again according to the needs desired by the user.